2014
DOI: 10.1123/jsep.2013-0206
|View full text |Cite
|
Sign up to set email alerts
|

Team Perfectionism and Team Performance: A Prospective Study

Abstract: Perfectionism is a personality characteristic that has been found to predict sports performance in athletes. To date, however, research has exclusively examined this relationship at an individual level (i.e., athletes' perfectionism predicting their personal performance). The current study extends this research to team sports by examining whether, when manifested at the team level, perfectionism predicts team performance. A sample of 231 competitive rowers from 36 boats completed measures of self-oriented, tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 54 publications
2
33
1
Order By: Relevance
“…Since Stoeber's (2012) review, there have been an additional three studies published that examined perfectionism and performance in sport (Hill, Hall, Duda, & Appleton, 2011;Hill, Stoeber, Brown, & Appleton, 2014;Thompson, Kaufman, De Petrillo, Glass, & Arnkoff, 2011). We describe these studies in detail below.…”
Section: Performance In Sportmentioning
confidence: 99%
“…Since Stoeber's (2012) review, there have been an additional three studies published that examined perfectionism and performance in sport (Hill, Hall, Duda, & Appleton, 2011;Hill, Stoeber, Brown, & Appleton, 2014;Thompson, Kaufman, De Petrillo, Glass, & Arnkoff, 2011). We describe these studies in detail below.…”
Section: Performance In Sportmentioning
confidence: 99%
“…1 Moreover, there is growing interest in other-oriented perfectionism beyond the role that it plays in dyadic perfectionism. For example, a recent study investigating perfectionism in sports teams (Hill, Stoeber, Brown, & Appleton, 2014) found that other-oriented perfectionism directed at one's teammates ("team-oriented perfectionism") showed significant differences between teams and positively predicted team performance in a competition. Another study investigating interpersonal citizenship behaviors in employees (Shoss, Callison, & Witt, 2015) found otheroriented perfectionism to interact with conscientiousness in predicting helping at work.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a reinvigorated interest in other-oriented perfectionism not only in research on personality and individual differences, but also in clinical psychology, applied psychology, and sport and exercise psychology (e.g., Ayearst, Flett, & Hewitt, 2012;A. Hill et al, 2014;Shoss, Callison, & Witt, 2015).…”
Section: Comparing Two Short Forms Of the Hewitt-flett Mpsmentioning
confidence: 99%
“…Finally, other-oriented perfectionism is an important form of perfectionism because it plays a key role in other conceptions of perfectionism such as dyadic perfectionism in the form of partner-oriented perfectionism (other-oriented perfectionism directed at one's partner; Habke, Hewitt, & Flett, 1999;Stoeber, 2012) and partner-oriented sexual perfectionism (other-oriented sexual perfectionism directed at one's partner; Stoeber & Harvey, in press;Stoeber, Harvey, Almeida, & Lyons, 2013) as well as team-perfectionism in the form of team-oriented perfectionism (other-oriented perfectionism directed at one's team members; A. Hill et al, 2014). Consequently, it is important to have a MPS short form that reliably captures all three dimensions of perfectionism of Hewitt and Flett's (1991) model, including other-oriented perfectionism.…”
Section: Comparing Two Short Forms Of the Hewitt-flett Mpsmentioning
confidence: 99%
See 1 more Smart Citation